"The Source of Learning is Thought" Reading the Chin-ssu lu (近思錄) with a "Western Eye". Issue 1 (2nd January 2016) - Reichenbach, Roland
Abstract: The contribution focuses on Neo-Confucian texts as collected by Zhu Xi (朱熹 1130–1200) and Lü Zuqian (1137–1181) and is a look from the 'outside', from the perspective of German theories of Bildung ('self-cultivation'). It aims at demonstrating that among other insights that today's readers may gather from Neo-Confucian literature, one aspect protrudes from others: that learning can be considered as a virtue—even a meta-virtue—a form of life and mode of self-formation of the person. It does not seem exaggerated, from this perspective, to state that Neo-Confucian philosophy is—to a large extent—a philosophy of learning and self-transformation which offers fruitful irritants for questioning the widespread habits of thinking about skills and their development in today's strong and problematic discourses and corresponding educational policies.